Tantangan Orang Tua dalam Mendampingi Proses Pembelajaran Anak (Studi Kasus di Kecamatan Picung Pandeglang Banten) - Aprilla, Mila; Tesniyadi, Dema (YASIN, 2022)
The purpose of this study is to describe how the challenges of parents in accompanying children during their special learning during the current pandemic where the role of parents is needed by children. This research is a descriptive qualitative research, this research involves parents, and teachers in Pandeglang District, Picung District. Collecting data in this study using direct interview and documentation techniques, in this study we can find out how the challenges faced by parents in accompanying children during learning at home, learning at home is carried out during a pandemic in this learning, parents and children must work together so that the learning process at home it goes well and is easy for children to do, there are many complaints from parents and children in carrying out the learning process as it is today, there are positive and negative impacts. In the implementation of online learning so that parents must be able to divide the time where the work of parents must be divided by time by accompanying their children during learning at home, parents must prepare learning equipment such as cellphones, laptops and internet quota. Parents must be able to participate in the child's learning process where parents must understand how to use zoom in children's learning activities, parents must be required to master technology which can be called a new learning system.